Development of a HPLC Method for the Estimation of Celecoxib in Human Plasma - Krishnaiah, Y.S.R.; Satyanarayana, V.; Bhaskar, P.; Raju, V. (Asian Journal of Chemistry, 2010)
Varying quantity of celecoxib (25 to 1500 ng) was added to drug-free human plasma (0.5 mL) and mixed with 0.5 mL of acetonitrile. The mixture was vortexed for 5 min and centrifuged at 3,000 rpm for 10 min and the supernatant liquid was filtered. Fifty microlitres of the resultant filtrate was injected into a reverse phase C-18 column using a mobile phase consisting of methanol and acetic acid (pH adjusted to 3.0 with dilute ammonia solution) in the ratio of 68 : 32% v/v at a flow rate of 1.5 mL/min. The eluents were monitored at 254 nm. The method was validated for its linearity, precision and accuracy. The present HPLC method was found to be simple, precise, specific, less time consuming and accurate for the estimation of celecoxib in human plasma.